Vefeyâtü’l-a’yân ve enbâ’u ebnâ’iz-zemân - 880-01 İbn Hallikân, 1211-1282. (Beyrut Beyrut Beyrut Beyrut Beyrut Beyrut Beyrut Beyrut)
8 cilt (1. c. 493 sayfa ; 2. c. 557 sayfa ; 3. c. 524 sayfa ; 4. c. 490 sayfa ; 5. c. 337 sayfa ; 6. c. 439 sayfa ; 7. c. 383 sayfa ; 8. c. 636 sayfa)